Connect how to use data and experience marketing to create lifetime customers - Petersen, Lars Birkholm (Wiley, 2014)
"Marketing is going through a revolution that rivals the impact of Gutenberg's printing press. Customers are in control and marketers have become an unnecessary annoyance. Smart marketers have learned to think in new ways, use new technology, and apply new processes. They've moved to a higher level that achieves their business objectives while being more relevant to the customer. In this "age of the customer," a marketer's message must be personal, relevant, and accessible at all touch points throughout a customer's life cycle, both online and offline. This takes new ways of thinking and new processes to be relevant to individual customers, to be accessible through multiple online and offline channels, and to link digital goals and metrics to business objectives. It's a tough new world of marketing, but Owning the Customer Experience takes you inside this world to see how the winners are jumping ahead of their competitors."--